MOTIVASI BELAJARWARGABELAJARDI HOMESCHOOLINGKAK SETO KOTA PEKANBARU - Ria Sartina; Jasfar Jas; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this research is how high is the motivation of learning citizens to learn in Homeschooling Kak Seto Pekanbaru City?. Then is there a variation in the learning motivation of citizens learning at Homeschooling Kak Seto Pekanbaru City based on gender, age, and package (A B)?. The purpose of this study was to determine the level of learning motivation of citizens learning in Homeschooling Kak Seto Pekanbaru City. As well as differences in learning motivation of citizens learning in Homeschooling Kak Seto Pekanbaru City based on gender, age, and package (A B). This study has 5 indicators, namely (1) the existence of a desire to learn, (2) future expectations, (3) a conducive learning environment, (4) encouraging students to learn, (5) giving direction to the learning activities of learning citizens. The population in this study were 40 people learning. The sample in this study used a saturated sampling technique. The sample in this study was taken from all residents learning package A and B in Homeschooling Kak Seto Pekanbaru City as many as 40 people and 20 people for the trial. The data collection technique in this study was a questionnaire technique. Out of 68 statement items tested, 4 invalid and 64 valid statements were found. Researchers discard invalid statements, because they do not interfere with other statements. Based on the results of the study5 indicators were obtained for each indicator of learning motivation of citizens learning in homeschooling Kak Seto PekanbaruCityall classified as high and medium, while in the study were more at high levels, because seen from the average final results. So residents learn to have high motivation to study at homeschooling Kak Seto Pekanbaru City.Key Words: Motivation, Learning Motivation Citizens Learn